2016
DOI: 10.1002/cnma.201600266
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Bionanocomposite Foams with a Chitosan Matrix Reinforced by Nanofibrillated Cellulose

Abstract: Multifunctional bionanocomposite foams with 3D interconnected networks showing advantageous mechanical properties, thermal insulation, underwater oleophobicity, and biocompatibility, were made from a chitosan matrix reinforced with nanofibrillated cellulose (NFC). The density of the NFC–chitosan nanocomposite foams can be controlled by varying the NFC/chitosan weight ratio and solid content of the suspension in the fabrication process. The mechanical properties and thermal stability of the nanocomposite foams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 62 publications
3
29
0
2
Order By: Relevance
“…1 and 11 MPa [BAS01]. Wang et al [Wan16] showed that adding cellulose nanofibres (CNF) to a chitosan-based solution one obtains improved mechanical properties of the resulting solid foams. We thus followed a similar route to improve the mechanical strength of the monodisperse chitosan foams.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 and 11 MPa [BAS01]. Wang et al [Wan16] showed that adding cellulose nanofibres (CNF) to a chitosan-based solution one obtains improved mechanical properties of the resulting solid foams. We thus followed a similar route to improve the mechanical strength of the monodisperse chitosan foams.…”
Section: Resultsmentioning
confidence: 99%
“…Conveniently, chitosan and CNF can be both dispersed in aqueous solutions, which facilitates the interpenetration of the chitosan chains and the CNF. As shown inFigure 2.28, Wang et al[Wan16] developed a templating method towards chitosan-CNF nanocomposite foams by freezing and freeze-drying a mixed dispersion of chitosan and CNF. This method is known as ice templating, and the pores result from the sublimation of ice crystals[Col09].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the past decade, efforts have been made for the development of renewable materials due to the surge to alleviate environment related concerns. Bio‐composites in this regard offer interesting properties and are relevant for a wide range of applications from flexible energy storage devices and optoelectronics to sensors, actuators, packaging and medical devices . In this regard, cellulose nanofibers (CNF) is emerging as next generation reinforcement bio‐polymer for fabrication of multifunctional bio‐composites .…”
Section: Introductionmentioning
confidence: 99%